Tailoring Photoluminescence from MoS2Monolayers by Mie-Resonant Metasurfaces - Bucher, Tobias; Vaskin, Aleksandr; Mupparapu, Rajeshkumar; Loechner, Franz J. F.; George, Antony; Chong, Katie E.; Fasold, Stefan; Neumann, Christof; Choi, Duk-Yong; Eilenberger, Falk; Setzpfandt, Frank; Kivshar, Yuri S.; et al. (ACS Photonics, 2019)
We experimentally investigate coupling of the photoluminescence (PL) from monolayers of MoS 2 to Mie-resonant metasurfaces consisting of silicon nanocylinders. By a systematic variation of the nanocylinder diameter, we sweep the metasurface resonances over the excitonic emission band of monolayer MoS 2 . We observe strong enhancement, as well as spectral and directional reshaping of the emission. By a comprehensive optical characterization, we unveil the different physical factors, including electronic, photonic, and mechanical influences, responsible for the observed PL changes. Importantly, we show that by geometrical tuning of the nanocylinder resonances, the emission can be tailored from occurring under very large angles to being directed out of the substrate plane. Our results highlight the need and potential of controlling not only the photonic, but also electronic and mechanical environmental factors for tailoring PL from TMD monolayers by integrating them in nanophotonic architectures.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D materials; dielectric nanoantennas; excitonic emission; light-emitting metasurfaces; Mie resonances; transition metal dichalcogenides